Transmigration program can be failed, but transmigrant stay life: Portraits of Transmigrant Families in Sorong Regency, West Papua - Irin Oktafiani; Herry Yogaswara (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
Transmigration has been applied in Indonesia as a development and population distribution strategy. Historically, the Indonesian transmigration program has a long story since the Ethical Policy until now. Furthermore, transmigration had been claimed and became the primary strategy of development in the New Order. Despite all the hope about transmigration, people considered this program failed nationally because its top-down system has caused a new problem in the destination area. However, some transmigrants have been succeeded and struggled in the new area. This paper described the bright side of what-so-called failed transmigration in Segun, Sorong, West Papua. Data are collected by multi-sited ethnography with observation and in-depth interviews of two successful Javanese families in Segun. In conclusion, this paper argues that although the program has failed nationally, each transmigrant had its strategy to survive and succeed in the new area.